Simulation of Virtual Tripwire Using Real Time Video Surveillance for the Security of Restricted Area - D. Wibawa, Adhi; H. Purnomo, Mauridhie (IPTEK The Journal for Technology and Science, 2007)
Recent development in the security world, video surveillance system has been used widely to protect the most valuable properties or restricted areas in the world. However, the old monitoring system usually only watch the Region of Interest (ROI) without any embedded systems that can trigger automatically the alarm when there are some suspected things happen. By using Virtual Tripwire, video surveillance system can protect safely and effectively the restricted area such as seaport, banking, jail, warehouse, automatic teller machine etc. Virtual tripwire is an algorithm to control the value of some certain pixels in fix position. Virtual tripwire is made of several points which make a rectangle in a captured frame. For the first time, system will take automatically one frame as reference by calculating each point in that rectangle and save them in some arrays. The second step is that in every second system will evaluate all points in the same position to measure weather there are some differences or not. These differences will trigger the alarm automatically. Virtual Tripwire is like a virtual border in the form of rectangle that can avoid everything to pass in a frame grabbed by producing sign.